Electromagnetic bone segment tracking in multiplanar osteotomies: a saw bone study - Geisbüsch, Andreas; Gramer, Carina; Dreher, Thomas; Hagen, Niclas; Hagmann, Sébastien; Renkawitz, Tobias; Götze, Marco (Journal of orthopaedic research, 2025)
Computer assisted orthopedic surgery is used to improve precision. Electro-magnetic tracking has been shown to improve precision in mono-planar derotational osteotomies. However, studies are lacking to investigate its use in multiplanar osteotomies. For this purpose, 60 complex (derotation and extension) osteotomies were performed in standardized sawbones. Correction amount was randomly planned before the procedures. In 30 bones, the amount of correction was determined intraoperatively using conventional goniometric measurement while in the other 30 bones electro-magnetic tracking was used to guide the amount of correction. CT-scans were done before and after the procedures in all bones and the amount of correction was determined to compare the precision of the two techniques. Electromagnetic tracking resulted in a precision of 2.25° ± 1.77° for derotation and 1.38° ± 1.29° for extension, while precision for the conventional method was significantly lower. There was a significant relationship between goniometer measurement deviation and the absolute angle change for derotation and extension measurements with larger deviations for greater angle changes. For the electro-magnetic tracking, this correlation was observed only for derotation measurement. Electro-magnetic tracking represents an accurate method to control complex, multiplanar corrective osteotomies with superior precision in comparison to conventional goniometric measurement. Further research is needed to investigate the in-vivo accuracy and the effects on clinical outcome.
Online veröffentlicht: 28. Oktober 2024
Gesehen am 11.04.2025